Gelatin/Carboxymethyl Cellulose Mucoadhesive Films with Lysozyme: Development and Characterization - Dekina, Svetlana (Carbohydr Polym, 2016)
The goal of our study is to develop and characterize mucoadhesive films with entrapped lysozyme based on gelatin/sodium carboxymethyl cellulose as perspective antimicrobial preparation. Lysozyme in mucoadhesive films retains more than 95 % of its initial activity for 3 years of storage. Different physical-chemical and biochemical characteristics of entrapped enzyme were evaluated, such as film thickness, weight, time of dissolution in water, bioadhesive force, in vitro lysozyme release, pH- and thermoprofiles of hydrolytic activity, effect of γ-sterilization, etc. We have shown that gelatin/sodium carboxymethyl cellulose films have adhesive force on the level of 4380 Pa. Scanning electron microscopy images shows the relative uniformity of the gelatin surface with entrapped lysozyme. Mucoadhesive films with lysozyme have 100% bactericidal effect on the test strain, Staphylococcus aureus ATCC 25923 F - 49 and thus could be considered as a perspective antimicrobial preparation.